Charcoal: a driver of dryland forest degradation in Africa? ICRAF Factsheet - World Agroforestry Centre (World Agroforestry Centre, 2013)
Wood has been used as fuel for millennia, meeting humanity’s basic needs for cooking, boiling water, lighting and heating. Today woodfuel, i.e. firewood and charcoal, accounts for around 10% of global energy supply, but it dominates energy provision in many parts of the developing world. In particular, the inhabitants of sub-Saharan Africa (SSA) benefit significantly from woodfuel, with the highest regional per capita consumption of 0.69 m3/year in 2011, 2.5 times higher than the global average of 0.27 m3/year. Over 90% of SSA’s overall population of 852 million and virtually 100% of the 535 million rural residents rely on woodfuel for energy.